Islamic Educational Leadership and Teacher Performance in Indonesian State Islamic Primary Schools - Putri, Anita; Patimah, Siti; Murtafiah, Nurul Hidayati; Abg. Abu Nawas, Abg. Ashmirul; Ahad, Ijaz (Universitas Islam Negeri Raden Intan Lampung, 2026)
Leadership quality in Islamic primary education is central to teacher professionalism, yet empirical evidence from Indonesian state madrasahs remains limited. This qualitative multi-site case study examines how Islamic school principals manage leadership practices and how these practices relate to teacher performance in three State Islamic Primary Schools (Madrasah Ibtidaiyah Negeri/MIN) in Lampung, Indonesia. Data were derived from observations, semi-structured interviews with principals and teachers, and institutional documents during May-June 2024; analysis followed data reduction, display, and verification with source, technique, and time triangulation. Findings show that leadership management operated through four connected functions: participatory planning, role-based organizing, motivational implementation, and continuous supervision. Teacher performance was reflected in lesson planning, curriculum enactment, classroom management, innovative pedagogy, assessment, individual feedback, character formation, and professional learning. Cross-site patterns indicate a participative-relational model in MIN 2 Pesawaran, an innovation-performance model in MIN 2 Bandar Lampung, and an exemplary-spiritual model in MIN 3 Lampung Selatan. Supportive factors included collaborative climate, parental/committee support, and teacher commitment; constraints included limited funding, administrative workload, unequal ICT access, and teacher rotation. The study contributes a context-sensitive model of Islamic educational leadership for teacher performance and inclusive quality education.